2021
DOI: 10.3390/foods11010030
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Peel Extracts for Industrial-Scale Production of Bio-Based Active Food Packaging

Abstract: The thermal stability of four different commercial citrus peel extracts was tested and improved by an encapsulation process with β-cyclodextrins in a spray-dryer. All extracts after the encapsulation process maintained a good antioxidant capacity, with an apparent loss in total phenolic compounds of around 20–25%. In addition, all samples showed good antimicrobial activity (MIC 5-0.625 mg/mL) against Staphylococcus aureus, which was maintained after the encapsulation process (MIC 5-1.25 mg/mL). Based on the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…The highest MIC, MBC, and MFC values were recorded in LP. Fiorentini et al ( 54 ) found that food-grade commercial citrus peel extract (5–0.625 mg/mL) inhibits the growth of Staphylococcus aureus , which was maintained after the encapsulation process (MIC 5–1.25 mg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…The highest MIC, MBC, and MFC values were recorded in LP. Fiorentini et al ( 54 ) found that food-grade commercial citrus peel extract (5–0.625 mg/mL) inhibits the growth of Staphylococcus aureus , which was maintained after the encapsulation process (MIC 5–1.25 mg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…The latter allowed us to putatively identify the phenolic compounds characterizing the OL extract and food simulants A and B after migration from the coated PLA films. The untargeted analysis was conducted as reported by Fiorentini et al [16]. Ferulic acid (phenolic acids), quercetin (flavonols), catechin (flavanols), cyanidin (anthocyanins), luteolin (flavones and other flavonoids), resveratrol (stilbenes), and oleuropein (for tyrosol derivatives and lower-molecular-weight compounds) were used as qualitative and quantitative standards of their respective classes.…”
Section: Untargeted Phenolic Profiling By Uhplc-hrms Approachmentioning
confidence: 99%
“…Based on the concentration of the commercial OL extract into the coating formulation (<50 mg/mL), the volume of the coated solution used for each coated PLA film (about 2 mL for 3.75 dm 2 surface), and the ratio between the coated PLA film and food simulants used for the migration tests (0.36 dm 2 in 36 mL), the maximum extract concentration that could potentially migrate into food simulants was evaluated. Moreover, the greatest concentration of the total equivalent phenolics that could migrate and the fractions of the migrated compounds were evaluated following the method reported by Fiorentini et al [16].…”
Section: Untargeted Phenolic Profiling By Uhplc-hrms Approachmentioning
confidence: 99%
See 2 more Smart Citations